Mythos e logos no poema de Parmênides - Conte, Bruno Loureiro (2010)
It is widely known that Parmenides Poem, which is considered a fundamental work in Greek philosophical thought, presents a plurality of mythical elements, and that its clarification constitutes an issue to the interpreters. This research is an investigation of the historical and philosophical meaning of mythos and logos in the Poem, considering the work in its cultural contexts. Our analysis begins by bringing to the foreground the presence of mythos, understood in its original sense of authorized way of speaking, pointing out its interweaving with logos, in such a manner that without the former the argument of the latter would remain incomprehensible. On the other hand, we aim to determine the specificity of logos in Parmenides: it shows up as a reflexive, refutative logos, but not, as some interpreters have sustained, a strict demonstration . Having established this point, Parmenides work shows itself as productive of a plurality of mythical assemblages, appropriating images of the traditional inspired poet, of initiation in cults of mystery, of divinity figures and of the Archaic Lyric conception of human existence. Furthermore, the Poem deploys itself in multiple discursive configurations: narration, argument, oracular speaking. In accordance to that, we introduce an interpretative hypothesis associating the Goddess speech in the Poem to a particular kind of oracle, similar to that of the mantic healer. Such associations or assemblages, nonetheless, are not simple reproductions of aspects already present in Greek culture: they are, as a matter of fact, subverted in the direction of the philosophically instituted radical reflection, which collects signals from visible and invisible, leading to thinking